2015
DOI: 10.1063/1.4931638
|View full text |Cite
|
Sign up to set email alerts
|

Flip channel: A microfluidic device for uniform-sized embryoid body formation and differentiation

Abstract: This paper reports a two-layered polydimethylsiloxane microfluidic device-Flip channel, capable of forming uniform-sized embryoid bodies (EBs) and performing stem cell differentiation within the same device after flipping the microfluidic channel. The size of EBs can be well controlled by designing the device geometries, and EBs with multiple sizes can be formed within a single device to study EB size-dependent stem cell differentiation. During operation of the device, cells are positioned in the designed posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A notable observation was that 2mu-VSV appeared to be silenced in the peripheral cells of EBs in the culture where the outgrowth of differentiated cells is expected. 25,26 We speculate that the maturation of the type I interferon pathway or other antiviral pathways in the differentiated cells clears VSV, as the differentiation progresses. This is a favorable property of 2mu-VSV for future applications as a transgene vector to induce stem cell differentiation.…”
Section: ■ Discussionmentioning
confidence: 97%
“…A notable observation was that 2mu-VSV appeared to be silenced in the peripheral cells of EBs in the culture where the outgrowth of differentiated cells is expected. 25,26 We speculate that the maturation of the type I interferon pathway or other antiviral pathways in the differentiated cells clears VSV, as the differentiation progresses. This is a favorable property of 2mu-VSV for future applications as a transgene vector to induce stem cell differentiation.…”
Section: ■ Discussionmentioning
confidence: 97%
“…In another example, at larger scales, the direction of stem cell differentiation was shown to be potentiated by the size of stem cell embryoid bodies generated in microfluidic wells (3,27). Studies by two independent groups have shown that small embryoid bodies remained inert to neurodifferentiation, whereas larger clusters (>250-350 μm in diameter) adopted a neural morphology with extensive neurite formation (Figure 3c) (27,31). The mechanism of this is still unclear and may or may not be due to diffusible signals, although the role of diffusible stem cell signals is being actively investigated (22,32).…”
Section: Predicting Patchy Switching In Response To Patch Sizementioning
confidence: 95%
“…Finally, true 3D patterning is now possible as a result of advances in biomaterials, chemistry, and 3D bioprinting, so that molecules and cells can be patterned on or within functionalized polymeric scaffolds or matrices for more realistic, tissue-like geometries (41)(42)(43)(44)(45). These patterning tools have been invaluable for evaluating the effect of patch size on blood coagulation (Figure 3a) (25) and stem cell differentiation (Figure 3c) (27,31,(46)(47)(48). Patterning can also distinguish the role of cell-cell contacts from that of soluble signaling (28) to help assess the extent to which transport-mediated signals drive a particular system.…”
Section: Microscale Control Over Transport Phenomena Controlling Patc...mentioning
confidence: 99%
“…Next, devices were rinsed with sterile phosphate-buffered saline (PBS) and then incubated with a 1 mg/ml bovine serum albumin (BSA; Millipore) solution for 30 minutes to passivate the surfaces. 33, 48 A 200 μL pipette tip filled with cell culture medium was placed at the device inlet for aggregate loading and perfusion. Aggregates were collected and resuspended at a concentration of approximately 600 aggregates/mL in a solution of 1.05 g/mL Percoll (Sigma Aldrich) in phosphate-buffered saline (PBS) to prevent rapid settling.…”
Section: Methodsmentioning
confidence: 99%